Could endoscopic ultrasound help in choosing the line of management of vascular rectal lesions? - Mostafa, Ahmed (Endosc Ultrasound, 2017)
We present a 55-year-old male with recurrent attacks of fresh bleeding per rectum, 3 intermittent bouts per year for the last 2 years. The last attack was severe; hemoglobin dropped to 7 g/dl necessitating blood transfusion. Colonoscopy revealed a rectal polyp, 1 cm × 1.5 cm, with bluish intact covering mucosa, compressible on palpation by a biopsy forceps, highly impressive of rectal hemangioma. No biopsies were taken for fear of bleeding. Rectal endoscopic ultrasound (EUS) showed a soft tissue polyp, 5 cm above the anal verge originating from the submucosal layer (3rd layer) with preserved deeper muscularis propria layer. Doppler study showed a feeding vessel at its base with venous color flow signal. The lesion was most probably localized rectal cavernous hemangioma. The treatment options for the localized type of GI hemangiomas include polypectomy with endoloop, ethanolamine oleate injection, cyanoacrylate (histoacryl) injection, or surgery. We avoided doing polypectomy with endoloop as it will carry a high risk of postprocedural bleeding after falling of the loop or band with exposure of the significant feeding vessel seen by EUS examination. As there was no role for vessel embolization by interventional radiology as the feeding vessel is vein and not an artery, we preferred to do ethanolamine oleate injection. Hence, EUS had direct implication on choosing the line of therapy of that case. 12 mL of 5% ethanolamine oleate were injected (4 injections, 3 mL each) by a usual sclerotherapy needle. No further bouts of bleeding per rectum for 3 months after the maneuver. CONCLUSION: Rectal EUS could help in choosing the line of management of vascular rectal polyps.